STANDARDIZED ENGLISH TESTS: KNOWLEDGE, ATTITUDE, AND PRACTICE OF MEDIOCRE UNIVERSITY’S ELT STUDENTS IN INDONESIA - Muhalim, Muhalim; Ardiana, Ardiana (Fakultas Keguruan dan Ilmu Pendidikan, 2017)
This research was conducted at Muhammadiyah University of Makassar as one of the universities classified in mediocre level based on the data of the Directorate for Higher Education (Ristekdikti). There were 8 English Education Department classes that were investigated; each class consisted of more or less 30 students. Thus, the total number of participants was 240 students. This research used stratified random sampling. There were two sampling classes in each even semester. Thus, the data were collected from students who were studying in the semester two, four, six and eight. The design of this research was cross-sectional survey. Questionnaire was employed to gain all the data needed in this research. The data gained were analyzed by using descriptive and inferential statistics. The result revealed that students have different dispositions towards standardized tests. The findings of the reseach show that among the three types of Tests, TOEFL PBT and iBT and IELTS, Students tend to show greater knowledge, more positive attitude and keener taking PBT TOEFL compared to the two other tests. While the growing demand of studying iBT and IELTS is increasing, students seem to still favor this kind of traditional test. The problem is even more complex because only small percentage of students show positive disposition toward PBT test, which has been now considered as an outdated test.